Characterization Of Genomic And Plasmid DNA Of Chlamydia psittaci Isolates - Sreeja R Nair (Department of Microbiology, College of Veterinary and Animal Sciences, 2001)
Four isolates of Chlamydia psittaci (M-28, M-430, M-121, P-156) obtained from ruminant abortion were subjected to restriction enzyme analysis and plasmid profiling to assess molecular level differences/homogenity among the isolates. The changes produced in developing chick embryo and the cytopathic effect in Me Coy cell line by the isolates were also investigated in this study. The C. psittaci isolates preserved in the Department of Microbiology were revived by passaging in embryonated chicken eggs through yolk sac route. Six to seven day-old developing chick embryo were used for propagation of the isolates. The isolates, M-28 and M-430 were found to produce death of the embryos within 10 days. The isolates M-121 and P-156 were not able to cause death within 10 days. The embryos appeared stunted with patchy haemorrhages all over the body and hyperemic legs. The yolk sac was thin walled, with deeply injected blood vessels and the yolk was thin and watery. M-28 and M-430 produced more severe lesions of the inoculated embryos compared with the other isolates. The isolates were grown in Me Coy cell line. All isolates revealed marked CPE, characteristic of C. psittaci, with rounding and clumping of cells to form syncytia at 48 h PI and formation of intra cytoplasmic inclusion bodies